Multiscale Turbulent Transport - Afonso, Marco Martins (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Turbulent transport is currently a prominent and ongoing investigation subject at the interface of methodologies from theory to numerical simulations and experiments, and it covers several spatiotemporal scales. Mathematical analysis, physical modelling, and engineering applications represent different facets of a classical, long-standing problem that is still far from being thoroughly comprehended. The goal of this Special Issue is to outline recent advances of such subjects as multiscale analysis in turbulent transport processes, Lagrangian and Eulerian descriptions of turbulence, advection of particles and fields in turbulent flows, ideal or nonideal turbulence (unstationary/inhomogeneous/anisotropic/compressible), turbulent flows in biofluid mechanics and magnetohydrodynamics, and the control and optimization of turbulent transport. The SI is open to regular articles, review papers focused on the state of the art and the progress made over the last few years, and new research trends.